The effects of music on helping behavior: A field study - North, Adrian; Tarrant, M.; Hargreaves, David (Sage Publications, Inc., 2010)
Several studies indicate that mood can influence the likelihood of an individual demonstrating instances of helping behavior, and one previous laboratory study has indicated that music can be used to bring about manipulations of mood to such an end. To investigate this in a naturalistic setting, 646 users of a university gym were played either uplifting or annoying music while theyworked out. Upon completionof theirworkout, they were asked to either sign a petition in support of a fictitious sporting charity (i.e., a low-cost task) or to distribute leaflets on their behalf (i.e., a high-cost task). Responses to the petition-signing measure indicated a ceiling effect with almost all participants offering to help. However, consistent with previous research on mood and helping behavior, uplifting music led to participants offering to help more on the high-cost, leaflet-distributing task than did annoying music.